2019
DOI: 10.11591/ijere.v8i4.20257
|View full text |Cite
|
Sign up to set email alerts
|

Identifying creative thinking skills in subject matter bio-chemistry

Abstract: <span>Creative thinking is needed in 21st century learning. This quantitative study aimed to determine whether chemistry education students at Universitas Jambi have the initial ability of creative thinking. The type of research that is used is a research design survey that is strengthened by the results of interviews to support the results of quantitative data. Where the number of all samples from this study was 188 college students with details of 140 female and 48 male college students from 4th semest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…Based on the research that has been done, it can be seen in Table 3 can be known that originality has the highest score. It is in line with the research by Wiwik et al, precentage of originality aspect is 43,1% and the highest between the other aspects (Ernawati et al, 2019). There is no significant difference in scores of originality aspect between male and female students.…”
Section: Originality Aspectsupporting
confidence: 92%
“…Based on the research that has been done, it can be seen in Table 3 can be known that originality has the highest score. It is in line with the research by Wiwik et al, precentage of originality aspect is 43,1% and the highest between the other aspects (Ernawati et al, 2019). There is no significant difference in scores of originality aspect between male and female students.…”
Section: Originality Aspectsupporting
confidence: 92%
“…Flexibility is the ability related to the number of ideas or answers generated, not only having many answers but the answers must be varied. This also relates to the way students solve problems where sometimes students can produce more than one answer (Ernawati et al, 2019). The low level of flexibility in this study was in line with Wartono et al (2018); Umar & Ahmad (2019) who also found that flexibility is the worst aspect belonged by students and prospective teachers.…”
Section: Moderatesupporting
confidence: 78%
“…The low ability of students on the flexibility aspect is due to several factors, namely 1) many students who are not able to solve questions and are only fixated on one way, 2) many students are not able to or lack motivation in solving open-ended questions, and 3) students only see a problem from one point of view (Faizah, 2018). Furthermore, according to Ernawati et al (2019), the low flexibility is caused by the students' answers coming from the same or less varied concepts. In this study, the low level of flexibility among the prospective chemistry teachers due to fewer chemistry concepts related to collision theory so the category idea produced tends to the same.…”
Section: Moderatementioning
confidence: 99%
“…To improve students' abilities and attitudes on science subjects, teachers must use learning models that support creative thinking (Ernawati, Muhammad, Asrial, & Muhaimin, 2019a). Improving the quality of education into a productive, creative, innovative, and effective generation through the integration of attitudes, abilities, and knowledge with life skills (Ernawati, Muhammad, Asrial, & Muhaimin, 2019b). Also, the influence of the development of information technology also affects students' fondness for reading.…”
Section: Introductionmentioning
confidence: 99%